Comparison of the Effects of Open Surgery and Minimally Invasive Surgery on the Achilles Tendon Rupture Healing Based on Angiogenesis. (1st September 2022) - Gong, Fan; Li, Xiaoliang; Zhang, Hanling; Wu, Jianke; Ma, Guoxu; Zhang, Bowen; Gao, Jian; Ding, Yi; Huang, Yonglu; Cheng, Suoli; Zhou, Xuebing; Zhao, Fei
Abstract : Objective . To compare the effect of three different surgical methods on rabbit Achilles tendon rupture. Methods . The Achilles tendon transection model was constructed by cutting off the inner half of the Achilles tendon. Rabbits were divided into 4 groups: model group, open surgery (OS) group, minimally invasive surgery (MS) group, and conservative treatment (CT) group. Biomechanical evaluation, H&E, and Picrosirius Red staining were applied to evaluate the histological changes and healing. RT-qPCR, Western blot, ELISA, and IHC staining were used to detect the expression of COLIII, IL-1 β, TNF- α, IL-6, CD31, VEGF, bFGF, and TGF- β 1. Results . Different surgery treatments significantly alleviated the histological changes in rabbits. The tension and elasticity of the Achilles tendon were significantly increased after surgery. In addition, surgery treatments notably alleviated the inflammatory responses in vivo via downregulation of IL-1 β, TNF- α, and IL-6 and promoted the tube formation in tissues through upregulating VEGF, bFGF, TGF- β 1, and CD31. Furthermore, MS exhibited best therapeutic efficiency on Achilles tendon rupture healing, compared with OS or CT. Conclusions . Our research revealed the superiority of MS in Achilles tendon rupture treatment at the molecular level compared with OS or CT.